Exploring perceptions of stroke survivors and caregivers about secondary prevention: a longitudinal qualitative study. Issue 14 (2nd July 2020) - Parappilly, Beena P.; Mortenson, William B.; Field, Thalia S.; Eng, Janice J.
Abstract: Purpose : To explore the changes in perceived barriers and facilitators associated with participation in secondary prevention activities of stroke survivors and their caregivers over the early stroke recovery period. Method : We conducted two individual interviews (at 2 weeks and 6 months post-discharge) with stroke survivors and their family members. Using purposive sampling, participants were recruited from the stroke units of two acute care hospitals. Results : About 11 male and 8 female stroke survivors and nine caregivers participated in the study. Thematic analysis identified three themes. (1) "A soul searching experience" indicating that the stroke was anxiety provoking leading to a soul searching experience into exploring its causes to adopt a healthy lifestyle; (2) "Old habits die hard" revealing that stroke survivors encountered barriers to adopt healthy lifestyle changes; (3) "Making a fresh start" recognizing that participants were motivated to make their lifestyle healthier and most sustained some lifestyle changes over the past 6 months. Conclusion : Despite experiencing some barriers, stroke survivors adopted lifestyle changes transitioning through different stages of change. Stroke prevention education and interventions from experts would be helpful later in the rehabilitation phase (once at home) and adopting a patient-family centered approach may assist stroke survivors and their caregivers in the uptake of secondary stroke prevention activities. Implications for rehabilitation: Stroke is perceived as a soul searching experience by stroke survivors and their caregivers motivating them to enquire its causes and adopting lifestyle changes to prevent a future stroke. Despite experiencing some barriers, stroke survivors adopted lifestyle changes transitioning through different stages of change. Stroke prevention education and interventions from experts would be helpful later in the rehabilitation phase (once at home). Adopting a patient-family centered approach may assist stroke survivors and their caregivers in the uptake of secondary stroke prevention activities.